Constitutive Activation and Inactivation of Mutations Inducing Cell Surface Loss of Receptor and Impairing of Signal Transduction of Agonist-Stimulated Eel Follicle-Stimulating Hormone Receptor - Byambaragchaa, Munkhzaya (Int J Mol Sci, 2020)
In the present study, we investigated the signal transduction of mutants of the eel follicle-stimulating hormone receptor (eelFSHR). Specifically, we examined the constitutively activating mutant D540G in the third intracellular loop, and four inactivating mutants (A193V, N195I, R546C, and A548V). To directly assess functional effects, we conducted site-directed mutagenesis to generate mutant receptors. We measured cyclic adenosine monophosphate (cAMP) accumulation via homogeneous time-resolved fluorescence assays in Chinese hamster ovary (CHO-K1) cells and investigated cell surface receptor loss using an enzyme-linked immunosorbent assay in human embryonic kidney (HEK) 293 cells. The cells expressing eelFSHR-D540G exhibited a 23-fold increase in the basal cAMP response without agonist treatment. The cells expressing A193V, N195I, and A548V mutants had completely impaired signal transduction, whereas those expressing the R546C mutant exhibited little increase in cAMP responsiveness and a small increase in signal transduction. Cell surface receptor loss in the cells expressing inactivating mutants A193V, R546C, and A548V was clearly slower than in the cell expressing the wild-type eelFSHR. However, cell surface receptor loss in the cells expressing inactivating mutant N195I decreased in a similar manner to that of the cells expressing the wild-type eelFSHR or the activating mutant D540G, despite the completely impaired cAMP response. These results provide important information regarding the structure–function relationships of G protein-coupled receptors during signal transduction.